RNA-Seq analysis of differential gene expression in Betula luminifera xylem during the early stages of tension wood formation - Cai, Miaomiao; Huang, Huahong; Ni, Fei; Tong, Zaikang; Lin, Erpei; Zhu, Muyuan (PeerJ, 2018)
Background Betula luminifera H. Winkler, which is widely distributed in southern China, is an economically important broadleaf tree species. However, little genomic information of B. luminifera is available, and little is known about the molecular mechanisms of wood formation in this species. Meanwhile, few efforts have focused on investigating the early transcriptional changes during tension wood formation in woody plants. Results A reference transcriptome dataset was first generated containing 45,700 Unigenes, and 35,135 (76.9%) Unigenes were annotated by a BLAST similarity search against four public databases. Then, based on an anatomical investigation, the global gene expression changes during the early stages of tension wood formation were analyzed. Gene expression profiling showed that a total of 13,273 Unigenes were differentially regulated during the early stages of tension wood formation. Most genes involved in cellulose and lignin biosynthesis were highlighted to reveal their biological importance in tension wood formation. In addition, the transcription levels of many genes involved in the auxin response pathway were significantly changed during the early stages of tension wood formation. Furthermore, 18 TFs co-expressed with key enzymes of cellulose synthesis were identified. Conclusions Our results revealed the transcriptional changes associated with TW formation and identified potential key genes in the regulation of this process. These results will help to dissect the molecular mechanism of wood formation and provide key candidate genes for marker-assisted selection in B. luminifera.
Keywords: RNA-Seq; Transcriptome; Betula luminifera; Tension wood formation; Auxin signaling pathway; Cellulose and lignin biosynthesis